ANALISIS TOKOH MINKE DALAM NASKAH DRAMA â€œBUNGA PENUTUP ABADâ€ ADAPTASI WAWAN SOFWAN - NIZAR MAULANA, FAHMI; HIDAJAD, ARIF (APRON Jurnal Pemikiran Seni Pertunjukan, 2020)
AbstractMinke is one of Pramoedya Ananta Toer character which is popular among activists, and literateur. His popularity is caused by His courage to fight for basic human rights through His written opinion on the newspaper, although in the end He had to accept His defeat, to be exiled and died in prison. His bravery is admired by His fans. Some people even use ?Minke? as their alias name in eeryday life. The journey of Minke, written in Pramoedya Ananta toer?s Pulau Buru Tetralogy has been adapted into a new medium such as movies and theater. One of them is Bunga Penutup Abad show which is succesfully held by Titi Mangsa Foundation from 2016-2018 in Jakarta?s Theater, Ismail Marzuki Park. In the past three years, Bunga Penutup Abad has never been devoid of spectators who have known Minke from Pramoedya Ananta Toer?s Pulau Buru Tetralogy.Data collection is done by observation, literature study, interview, and documentation. Data Analysis used is data reduction, and data presentation.The result of tHis study is to explicate Minke?s character in accordance with the rules, namely the aspects of characterization, such as psychological, sosiological, physiological, Minke?s position as a character in the playscript, and look for the character uniqueness so that him is loved by people. Psychologically, Minke character development can be devided into two, the first one is before Annelies gone, and the second is, after Annelies gone. Sosiologically, Minke comes from a group of native nobility who is faced difficulties in socializing with people around him, because His perspective is different from any natives. Physiologically, Minke has Javanese people typical physical appereance, which is brown skinned, and wearing Surakarta?s Javanese traditional clothing as everyday outfit. Minke?s position in the playscript, is protagonist whom is complexly written so, He is able to get emphaty from the audience.Keywords: Minke, Bunga Penutup Abad, Analysis, Character